Solar Geometry Factor in the Traditional Banjar “Bubungan Tinggi” House - Ikhsan, M. Rizki; Siska, Madschen Sia Mei Ol; Hidayah, Nur; Rizali, Muhammad; Halimah, Mahda (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The Banjar tribe in South Kalimantan has a traditional Bubungan Tinggi house, which is intended for nobles. This house is made of wood, in the form of a stilt with one roof angled upwards. This paper examines the solar geometry factor on the high ridge house, which is found on the pointed roof having a small geometric factor, so that the solar energy absorbed on the taper roof is small. This proves the local wisdom of the community in getting thermal comfort in their homes.